LINTAS SEJARAH PEMBANGUNAN PEREKONOMIAN DALAM ASPEK NEGARA HUKUM - Suardita, I Ketut; S, Adrie; PRATAMA, I PUTU ANDIKA (Jurnal Yustitia, 2023)
The state in its capacity as a rule of law has a role in economic development. This researchis a doctrinal research used by historical and analytical approaches. With the occurrence of “TheGreat Depression”, the role of the state is needed in the welfare of its people so that the concept ofthe Welfare State is born. Although considered good, the policies of the Welfare State concept areconsidered detrimental to the state, especially in the economic field. The existence of the conceptof Good Governance, can always improve the economic system which begins with improvingthe bureaucratic system, namely by implementing deregulation and de-bureaucratization.Deregulation and de-bureaucratization are things that need to be implemented in order to realizepeople’s welfare in accordance with the characteristics of good governance.